Mark Twain : American humorist - Wuster, Tracy (Mark Twain and his circle series., 2016)
"Mark Twain, American Humorist examines the ways that Mark Twain's reputation developed at home and abroad in the period between 1865 and 1882, years in which he went from a regional humorist to national and international fame. In the late 1860s, Mark Twain became the exemplar of a school of humor that was thought to be uniquely American. As he moved into more respectable venues in the 1870s, especially through the promotion of William Dean Howells in the Atlantic Monthly, Mark Twain muddied the hierarchical distinctions between class-appropriate leisure and burgeoning forms of mass entertainment, between uplifting humor and debased laughter, and between the literature of high culture and the passing whim of the merely popular"--Publisher's website